A dyadic analysis of loneliness and health-related quality of life in Latinas with breast cancer and their informal caregivers. Issue 2 (4th March 2019) - Segrin, Chris; Badger, Terry A.; Sikorskii, Alla
Abstract: Objective: The primary aim of this investigation is to provide a novel dyadic test of a model of loneliness and health-related quality of life (HRQoL) in a sample of Latinas with breast cancer and their informal caregivers. Design: At baseline, dyads completed measures of loneliness and HRQoL. At a 3-month follow-up, they returned to complete the HRQoL measure. Associations were tested with the Actor–Partner Interdependence Model. Sample: About 234 Latinas with breast cancer diagnosed within the past year and their informal caregivers participated in the investigation. Findings: Loneliness was concurrently and negatively associated with HRQoL at baseline for both survivors and caregivers. Survivors' baseline loneliness, controlling for their baseline HRQoL, negatively predicted their HRQoL at 3 months. Survivors' HRQoL at baseline also predicted caregivers' HRQoL at 3 months. Conclusion: Loneliness is a risk factor for declines in HRQoL among cancer survivors. Their caregivers are also at risk for degraded HRQoL when the survivor experiences compromised HRQoL. Loneliness complicates the HRQoL of the cancer survivor–caregiver dyad.